The Training and Assistance for Junior High School Science Teachers in Making Animated Videos through Canva Application - Siahaan, Sardianto Markos; Patriot, Evelina Astra; Lestari, Yora Inda; Simarmata, Ruth Helen; Jannah, Fathya Nurul; Nugraha, Ari Guna; Hartati N, Yendri Tri; Yuliani, Evi; Feranti, Hanisa; Putriani, Anjeli; Husna, Hafizhah Aulia (Unram Journal of Community Service, 2024)
The rapid development of technological advances has changed the paradigm in education, especially in learning innovation. This service aims to improve the quality of teachers in designing and making products in the form of animated videos. The technological innovation guided in this service is to produce animated videos as learning media. Participatory Action Research (PAR) is a method used in the implementation of service activities with stages: 1) giving an initial test, 2) service implementation activities, 3) evaluation and reflection stages, and 4) then giving the final test. The target participants of the service activities were the MGMP teacher community of science subjects in Palembang City. Based on the data obtained, there is an increase in test results with an N-gain of 0.56 which is included in the moderate category. Based on the above results, the training participants strongly agreed that this service activity could improve the skills and insights of teachers in making animated videos as science learning media